Pengaruh sanitasi lingkungan fisik rumah, sosial budaya dan kontak serumah terhadap kejadian Tuberkulosis Paru di Pulau Bengkalis Kabupaten Bengkalis - Melia Setia Rindu; Agrina Agrina; Ridwan Manda Putra (SEHATI: Jurnal Kesehatan, 2022)
The degree of public health is influenced by four factors, namely environment, behavior, health services, and heredity. Data from 2019 WHO Global Tuberculosis Report, Indonesia ranks third with the highest tuberculosis cases in the world. The purpose of this study was to analyze the sanitary conditions of the house environment (temperature, humidity, type of floor, ventilation, lighting), socio-culture (trust), and household contact against the incidence of pulmonary tuberculosis on Bengkalis Island. This research is an analytical study with a case-control design. This research was conducted on Bengkalis Island, namely in two sub-districts (Bengkalis District and Bantan District) and in the working area of Puskesmas Bengkalis, Puskesmas Pematang Duku, Puskesmas Selatbaru and Puskesmas Teluk Pambang. The data used are quantitative data sourced from observations, interviews, and questionnaires. The research sample was 80 people consisting of 40 cases and 40 controls. Data analysis was performed by multiple logistic regression tests. The results of the study concluded that the most dominant variable affecting the incidence of pulmonary tuberculosis was temperature with a p-value of 0.008. Confounding variables for tuberculosis incidence were ventilation, floor type, lighting, and confidence. The multivariate model formed is fit/fit for use. Based on the results of the calculation of the equation, it can be concluded that if a person has temperature risk factors, humidity risk factors, ventilation risk factors, floor type risk factors, lighting risk factors, trust risk factors, and household contact risk factors, then he will have a chance of suffering from pulmonary tuberculosis by 94 percent (with a probability value of 0.94).